Antifungal activity of endophytic bacteria controlling Fusarium verticillioides in maize - Castro de Ángel, Epifanio; Hernández-Castillo, Francisco Daniel; Gallegos-Morales, Gabriel; Ochoa-Fuentes, Yisa María (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this research was to know the antifungal activity of two endophytic isolates of Bacillus amyloliquefaciens against Fusarium verticillioides under laboratory and greenhouse conditions. In vitro dual cultures inhibition of phytopathogenic fungus was detected in a range of 59 to 62%. The endophytic bacteria reduced F. verticillioides incidence and severity more than 80% in plants that received the treatment compared to the control. The individual application of endophytic bacteria increased the chlorophyll content in leaves more than 150% compared to the control. Chlorophyll levels, stem diameter and fruit weight increased in all plants that received the antagonist strains treatment. The molecular corroboration of bacterial strains indicated 99% of identity withBacillus amyloliquefaciens contained in GenBank database with access codes KU570451.1 and KX665550.1.